The Bergen Facebook addiction scale: a reliability generalization meta-analysis - Ma, Jian-Ling; Jin, ZhengCheng; Liu, Chang (Frontiers in Psychology, 2025)
The Bergen Facebook Addiction Scale (BFAS) is a screening instrument frequently used to evaluate Facebook addiction. However, its reliability varies considerably across studies. This study aimed to evaluate the reliability of the BFAS and its adaptation, the Bergen Social Media Addiction Scale (BSMAS), and to identify which study characteristics are associated with this reliability. We performed a reliability generalization meta-analysis involving 173,641 participants across 127 articles, which reported 147 Cronbach's alpha values for internal consistency. The random-effects model revealed that the pooled Cronbach's alpha values were 0.8535 (95% CI [0.8409, 0.8660]) for the BFAS and 0.8248 (95% CI [0.8116, 0.8380]) for the BSMAS. Moderator analyses indicated that the mean and standard deviation of the total scores accounted for 10.06% and 36.7% of the total variability in the BFAS alpha values, respectively. For the BSMAS, the standard deviation of the total scores and sample size accounted for 13.54% and 10.22% of the total variability alpha values, respectively. Meta-ANOVA analyses revealed that none of the categorical variables significantly affected the estimated alpha values for either the BFAS or BSMAS. Our findings endorse the BFAS and BSMAS as reliable instruments for measuring social media addiction.